KEKUATAN EKSEKUSI HAK TANGGUNGAN SEBAGAI JAMINAN PENGEMBALIAN UTANG PEMBIAYAAN BERMASALAH PADA PRAKTIK PT. BANK MUAMALAT INDONESIA, TBK CABANG MEDAN - Sherhan Sherhan; Tan Kamello; Mahmul Siregar; Hasim Purba (USU LAW JOURNAL, 2014)
ABSTRACT   The spirit of the birth of the Mortgage Act was a solution for the banking sector in terms of having control collateral that debtor financing problems as a source returns. After doing research on practice in PT Bank Muamalat Indonesia, Tbk which carry out executions Mortgage as a loan repayment guarantees for customers financing  problems and the results are not significantly the maximum. Parate execution and real implementation of execution has its own weaknesses and loopholes. Parate execution as UUHT has advantages in terms of legal loopholes guarantee control assets that are still occupied because mandatory evacuation filed suit to state court of domicile, in addition to the implementation of parate execution may also lead to a lawsuit or opposition from its own customers with reasons to be implemented through the courts. While the implementation of the execution of real legal certainly for directly by the district court through the command chair of the district court, but the process will take a long time because it must go through several stages of the process execution like Aanmaning, Determination confiscation execution, Execution of confiscation execution, Determination and the auction process. It’s make obstacles for the Bank's business turnover in healthy NPF (Non Productive Financing), this is a problem for the Bank in disbursing financing to the community. Keywords : Financing problems, Mortgage, Parate Execution, Real Execution